PEMAKNAAN KHALAYAK TERHADAP PERFORMATIVITAS GENDER DALAM FILM KUCUMBU TUBUH INDAHKU - Erica Pinasthika, Emilia; Hasfi, Nurul; Manalu, Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study was conducted to understand the interpretation of millennial parents in Semarang City regarding gender performativity in the film